Implementasi Program Kalimasada Pada Pembaruan Status Perkawinan Tidak Dicatat Di Kecamatan Siwalankerto - Jannah, Roudhotul; Supriyono, Supriyono (International Journal Administration, Business & Organization, 2024)
The purpose of the study was to determine the extent of the effects of the implementation of the KALIMASADA program in updating the unregistered marital status conducted by the author on residents contained in the KALIMASADA target data in Siwalankerto Village. The method used in this research is a qualitative approach with a descriptive type of research based on measuring the criteria for successful implementation according, to George C Edward III, based on the variables of communication, resources, disposition, and bureaucratic structure. Data collection through observation, interviews, and literature studies of previous research. Here, the author carries out activities in the MSIB (Certified Independent Study Internship) program in collaboration with the Surabaya City Dispendukcapil. The author is the implementer of activities in the MSIB program in partnership with the Surabaya City Dispendukcapil as Population Administration Service Facilitator in Siwalankerto Village, Woncolo District, Surabaya City. The results showed that the implementation of the program has been running quite well. Communication between implementers creates thoughts that are in line with the achievement of program goals, related resources are qualified in terms of the use of technology for socialization purposes, implementers understand the roles and responsibilities given, and the maintenance of continuous monitoring, which makes progress in updating target data increase to 73%.